News Commentaries December 1960 - Abrahams, Peter (My University, 1960)
News commentaries broadcast in December of 1960. List of subjects included at the beginning.
55 pgs. Typescript, letter-sized, sepia-toned, in fairly good condition.
Keywords: Wright, Richard, 1908-1960; Police – Jamaica; Police – Complaints against – Jamaica; Legislative bodies – Jamaica; Labour unions – Jamaica; Commonwealth countries